Theoretical design of porphyrin dyes with electron-deficit heterocycles towards near-IR light sensitization in dye-sensitized solar cells. (August 2019) - Li, Wei; Ren, Wenhui; Chen, Zhi; Lu, Teng-Fei; Deng, Lei; Tang, Jianfeng; Zhang, Xingming; Wang, Liang; Bai, Fu-Quan
Highlights: Promising porphyrin sensitizers with electron-deficit heterocycles moieties are developed. Various factors govern the efficiency of DSSC are discussed in detail. Introduction of electron-deficit heterocycles results in great light-harvesting ability towards near-IR light sensitization. All developed dyes would be promising for DSSCs application. Abstract: We develop a series of porphyrin sensitizers with electron-deficit heterocycles based on the well-known YD2-o-C8 dye for application in dye-sensitized solar cells with the help of ab initio density functional theory calculations and quantum dynamics simulation based on the tight-binding extended Hückel Hamiltonian at the semiempirical level. The calculation results show that introduction of electron-deficit heterocycles into the porphyrin dyes can remarkably red-shift and broaden the Q band of the absorption spectrum and extend the coverage into near-infrared region, improving the light-harvesting ability. The key parameters influencing the photocurrent and photovoltage performance such as maximum short-circuit photocurrent ( J SC max ), intramolecular charge transfer, interface electron injection, and the shift of TiO2 conduction band edge ( Δ ECB ) are superior to YD2-o-C8 dye. Therefore, the designed sensitizers would be promising candidate for utilization in dye-sensitized solar cells.